The Function of Museum Pedagogy in the Development of Artistic Appreciation - Matjaž Duh (University of Maribor Press, 2015)
Contemporary museum pedagogy is located spatially in museums and galleries, which represent an authentic space for art. Artistic artefacts on display constitute an excellent basis for the development of art appreciation among children and young people. This means that the role of museum educators is not limited merely to classification, managing and presentation of art collections, but is also focused on in-depth educational work. Museum pedagogy must follow the guidelines of contemporary art-pedagogical practice, based on the development of productive and receptive skills among pupils and students. The simultaneous development of both skills is a prerequisite for discussing the development of artistic abilities. In the perception and reception of works of art, participants reach their own individual artistic interpretations of the given works of art. The method of aesthetic transfer emerges as the most appropriate didactic approach.